Socialist competition in the field of propaganda of the Soviet power in the field of economic exploitation (Eurasian Research Bulletin, 2022)
The article deals with the activities of the department of propaganda and agitation of the Soviet government and socialist competitions in the exploitation of the economy of Uzbekistan in 1953-1956.